BULIMIA NERVOSA BETWEEN ISLAMIC LAW AND HEALTH PERSPECTIVE - Rustam, Suhartina; Sabir, Muhammad; Qayyum, Abdul Rahman (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
The purpose of this research is to 1) determine the factors that influence the employees of Bank Axa Mandiri Makassar City to carry out Bulimia Nervosa. 2) To formulate the prevention and treatment of bulimia nervosa. 3) To indetify the harm of bulimia nervosa behavior in terms of health and Islamic law aspects. Answering these problems, the author uses the health and syar’i approach. The health approach is used because it refers to the scope of Islamic law. This type of research is qualitative research (field research), then a sociological (community) approach technique by examining the field’s facts. This study’s results indicate the factors that cause the employees of the Makassar City Axa Mandiri Bank to commit Bulimia nervosa, namely because of the demands of their work and wanting to satisfy their appetite. In terms of health aspects, the harmful behavior of bulimia nervosa can cause various diseases. As for the behavior of bulimia nervosa in terms of Islamic law, it is an act that is prohibited and makes the perpetrator will get a sin. Bulimia nervosa prevention can be done with gratitude, increased self-confidence, being realistic, adjusting eating patterns, and socializing. Several steps can be taken to take action to treat bulimia nervosa with psychologist therapy.